2021
DOI: 10.1016/j.talanta.2020.121718
|View full text |Cite
|
Sign up to set email alerts
|

Review: Detection and quantification of proteins in human urine

Abstract: Extensive medical research showed that patients, with high protein concentration in urine, have various kinds of kidney diseases, referred to as proteinuria. Urinary protein biomarkers are useful for diagnosis of many health conditions – kidney and cardio vascular diseases, cancers, diabetes, infections. This review focuses on the instrumental quantification (electrophoresis, chromatography, immunoassays, mass spectrometry, fluorescence spectroscopy, the infrared spectroscopy, and Raman spectroscopy) of protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
54
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(66 citation statements)
references
References 197 publications
1
54
0
1
Order By: Relevance
“…Urine contains many disease biomarkers that reflect an individual’s health status and that are good indicators of kidney disease [ 33 ]. Recent studies have reported that many types of kidney diseases, such as primary IgAN, lupus nephritis, and minimal change nephropathy, could be detected by biomarkers in urinary sediment [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Urine contains many disease biomarkers that reflect an individual’s health status and that are good indicators of kidney disease [ 33 ]. Recent studies have reported that many types of kidney diseases, such as primary IgAN, lupus nephritis, and minimal change nephropathy, could be detected by biomarkers in urinary sediment [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…RS gives a classifying “fingerprint” of an EV sample, indicating changes in proteins, lipids, and nucleic acids, while Mass spectroscopy provides much more detailed analysis of sample molecular composition. While RS does not offer as extensive information about EV samples as quantitative proteomics, it has clear advantages towards clinical diagnostics, due to its relative rapidness and lower workload 51 . Though it is rather challenging to make direct comparison between results obtained by using RS and proteomics studies, certain spectral peaks noted in RS may indicate characteristic features of protein composition.…”
Section: Discussionmentioning
confidence: 99%
“…Highly sensitive and selective identification and quantification of proteins are crucial due to their great importance for medical research and disease diagnoses in indicating pathological biological conditions [ 1 , 2 ]. For example, albumin in human urine has a significant value in the diagnoses of diabetic nephropathy, cardiovascular and renal disease [ 3 ]. During current pandemic period, IgG and its antibody provide reliable biomarkers related to COVID-19 [ 4 , 5 ], their detection can help prevent and control the virus infection at an early stage.…”
Section: Introductionmentioning
confidence: 99%